Disciplining Women: Feminism or Women's Studies - Elam, Diane (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1995)
In the context of the university's disciplinary organization, this essay analyzes the epistemological and programmatic relationships between women's studies, feminism and deconstruction.